Decline, adaptation or transformation: new perspectives on demographic change in resource peripheries in Australia and Sweden - Carson, Dean B.; Carson, Doris A.; Porter, Rob; Ahlin, Celia Yoshida; Sköld, Peter (DEU, 2017)
"Many sparsely populated resource peripheries in developed countries are perceived to suffer from periods of demographic decline due to loss of employment opportunities and services, youth out-migration and population ageing. While these trends tend to apply at broad regional scales and for particular time periods, diverse patterns of demographic change may be apparent if different spatial, temporal and social scales of analysis are taken into consideration. Comparing the experiences of two case study regions in northern Sweden and inland South Australia, this paper proposes an alternative conceptual framework to the 'discourse of decline', which could be used to examine the nuances of demographic change within resource peripheries. The framework includes spatial scale considerations that contrast broader regional demographic patterns with the experiences of sub-regions and individual settlements. It also includes temporal scale aspects, examining demographic change over different time periods to understand the pace, duration and frequency of population growth and decline. The framework finally includes social unit considerations, emphasising that demographic change affects different social groups in different ways. The results of the case studies suggest that considering demographic change as adaptation or transformation rather than decline may be more useful for identifying new - and qualitatively different - demographic pathways that emerge over time." (author's abstract)